The Role of Teachers in Enhancing Professional Development at SMA Negeri 2 Banda Aceh - Hidayat, Rahmat; Ansari, Bansu Irianto; Sari, Siti Mayang (Yayasan Pendidikan Bima Berilmu, 2026)
This study aims to describe the role of teachers in the development of professionalism at SMA Negeri 2 Banda Aceh. Teacher professional development is a crucial factor in improving the quality of learning and overall educational outcomes in schools. This research employed a descriptive qualitative approach, with teachers at SMA Negeri 2 Banda Aceh as the research subjects. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The results indicate that teachers play an active role in developing their professionalism through various activities, including the enhancement of pedagogical, professional, social, and personal competencies. Teachers are also involved in professional development activities such as training programs, workshops, group discussions, and the use of technology in the learning process. However, several challenges were identified, including limited time and insufficient supporting facilities. The study concludes that teachers have a significant role in professional development, and support from school management is essential to create a conducive environment for sustainable improvement of teachers’ competence and professionalism.